PERAN BIMBINGAN DAN KONSELING DALAM MENANGGULANGI KENAKALAN SISWA - IBNUDIN FAUZAN (Fakultas Agama Islam Universitas Wiralodra, 2020)
This resear aims to explore: (1) the role of guidance and conselling to cure student delinquency and (2) the implication of implementation of guidance and conselling to cure student delinquency.this research was qualitative approach by case studies. The data were obtained by depth-interview, participant observation, and documentation. The results showed that: (1) guidance and counseling have a very strategic role in learning activities which carried out in schools, the implementation of counseling can be integrated with various other activities in the school environment; (2) the impact of counseling activities can be the main forum for channeling students' interests and talents, thus the role and function of counseling is as the prevention process and treatment of various problems in learning